We have to solve f(x) > -1 for f(x)=(x-1)(x+1)/(x+2)(x-2)

f(x) > -1

=> (x-1)(x+1)/(x+2)(x-2) > -1

=> (x-1)(x+1) > -1*(x+2)(x-2)

=> x^2 - 1 > -1* (x^2 - 4)

=> x^2 - 1 > -x^2 + 4

=> 2x^2 > 5

=> x^2 > 5/2

=> x > sqrt 5/2 or x < -sqrt 5/2

**Therefore x lies in (-inf , -(sqrt 5)/2) and ((sqrt 5)/2 , + inf)**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now